Uma política pública de privatização e degradação da Amazônia disfarçada de regularização fundiária: uma análise sobre a evolução da Lei Federal nº 11.952/2009 - Paulo Roberto Cunha (Confins)
This paper analyzes the main changes in Brazilian Law no. 11,952/2009, known as the Amazon Public Policy for Land Regularization (PRFA), demonstrating that the Brazilian Government has been implementing a public policy of privatization of illegally invaded federal lands (land-grabbing), causing damage to the rural land structure and for the environment of the region.